Perspektif dan Dukungan Masyarakat Terhadap Rencana Pendirian Perguruan Tinggi Baru di Wilayah Penyangga IKN Nusantara - Abu, Ilham; Sultan, Muhammad (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
Transfer of IKN to East Kalimantan will be both an opportunity and challenge, especially the needs of new tertiary institutions in IKN supporting areas. This study aims to determine the perspective and support of the community towards the plan to establish a higher education institution in the archipelago's IKN buffer zone. This research uses a quantitative descriptive method with the population is Samarinda City residents of 825,494 people with a sample size of 400 people selected by Proportional Random Sampling. The data collected was then processed and analyzed descriptively in the form of frequency distribution tables and graphs accompanied by narration. The results of the study show that most of the people of Samarinda City have a positive perspective and support the plan to establish a new higher education institution in the IKN Nusantara buffer zone located in Samarinda City. Therefore, Mulawarman University and its formation team need to prepare strategic steps that are considered important and prioritized regarding the plan to establish Nusantara State University.